PENGEMBANGAN BAHAN AJAR MATERI PECAHAN BERBASIS PMRI MENGGUNAKAN KONTEKS WISATA MUSI RAWAS - Safitri, Catur Indah; Sukasno, Sukasno (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2024)
This research focuses on the utilization of teaching materials in mathematics concerning fractions that are less engaging and fail to connect mathematical concepts with concrete and beneficial situations in students' lives. The aim of this study is to create a teaching product on Fractional Material using the PMRI approach and linking it with the Musi Rawas Tourism Context, which is not only scientifically valid but also easily applicable in practice. The research was conducted in Grade V at Elementary School 58 Lubuklinggau. This study is a developmental research that utilizes a development model adapted from the Four-D model. This model consists of four stages, namely: 1) the definition stage, 2) the design stage, 3) the development stage, and 4) the dissemination stage. Data were collected through interviews and questionnaires. Evaluation by experts yielded validation scores of 0.82 for language experts, 0.84 for media experts, and 0.73 for subject matter experts, with an average score of 0.80. Meanwhile, the analysis of teacher practicality showed an average score of 0.90, and for student practicality, the average score was 0.87. Therefore, it can be concluded that the Teaching Material on Fractions Based on PMRI and Utilizing the Musi Rawas Tourism Context has met the standards of validity and practicality, making it suitable for implementation in the learning process regarding fractions.